Doped hole transport layer for efficiency enhancement in planar heterojunction organolead trihalide perovskite solar cells. (July 2015) - Wang, Qi; Bi, Cheng; Huang, Jinsong
Abstract: We demonstrated the efficiency of a solution-processed planar heterojunction organometallic trihalide perovskite solar cell can be increased to 17.5% through doping the hole transporting layer for reducing the resistivity. Doped Poly(triaryl amine) (PTAA) by 2, 3, 5, 6-Tetrafluoro-7, 7, 8, 8-Tetracyanoquinodimethane (F4-TCNQ) reduced device series resistance by three-folds, increasing the device fill factor to 74%, open circuit voltage to 1.09 V without sacrificing the short circuit current. This study reveals that the high resistivity of currently broadly applied polymer hole transport layer limits the device efficiency, and points a new direction to improve the device efficiency. Graphical abstract: Highlights: Perovskite solar cells (PSC) with high efficiency of 17.5% were fabricated. It reveals the low conductivity of currently used polymer HTL limits PSC efficiency. Doping the HTL increased device fill factor and enhanced device efficiency